White Collar Unions in Denmark - Blum, Albert; Ponak, Allen (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1974)
In this paper, the authors present evidence as to why the Danish experience may be relevant to those concerned with the issue of white-collar unionization.